10d-6=4s-15-3d

Simple and best practice solution for 10d-6=4s-15-3d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10d-6=4s-15-3d equation:


Simplifying
10d + -6 = 4s + -15 + -3d

Reorder the terms:
-6 + 10d = 4s + -15 + -3d

Reorder the terms:
-6 + 10d = -15 + -3d + 4s

Solving
-6 + 10d = -15 + -3d + 4s

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '3d' to each side of the equation.
-6 + 10d + 3d = -15 + -3d + 3d + 4s

Combine like terms: 10d + 3d = 13d
-6 + 13d = -15 + -3d + 3d + 4s

Combine like terms: -3d + 3d = 0
-6 + 13d = -15 + 0 + 4s
-6 + 13d = -15 + 4s

Add '6' to each side of the equation.
-6 + 6 + 13d = -15 + 6 + 4s

Combine like terms: -6 + 6 = 0
0 + 13d = -15 + 6 + 4s
13d = -15 + 6 + 4s

Combine like terms: -15 + 6 = -9
13d = -9 + 4s

Divide each side by '13'.
d = -0.6923076923 + 0.3076923077s

Simplifying
d = -0.6923076923 + 0.3076923077s

See similar equations:

| 3(5-4a)=99 | | 6x+5+4x-3=122 | | -92=4(3k-2) | | 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 | | 224=d-12 | | (33*5280)/(60) | | 70=al | | 6r+9=16+7r | | 9x^2-11x-2=0 | | x-5=1/12 | | (16y^3/8y^4)^-4 | | 12+6x=5x+6 | | 2(3x-4)=118 | | (4-1/2c)-1/3[3/4(1-2c)]1/12c | | 2x+5=-4x-6 | | (64m^1/2n÷m^-2n4/3)^1/2 | | 203/x=7 | | x/21=21 | | 4x+6=-2x-6 | | 14y^2-12y+3=0 | | e^2x=-4x | | .30x+6y=200 | | 3.5y-2.5y-6.3=-1.0-2.5 | | 2x+3-8(x+1)=3x+2 | | 5q+6=20 | | -3r+10=15r+3g |

Equations solver categories